1987
DOI: 10.1038/329839a0
|View full text |Cite|
|
Sign up to set email alerts
|

No requirement of cyclic conformation of antagonists in binding to vasopressin receptors

Abstract: Early reports that acyclic analogues of oxytocin and vasopressin (AVP) have drastically reduced agonistic activities established as dogma that an intact hexapeptide ring structure is essential for the pharmacological activities of analogues of neurohypophysial hormones. Thus, virtually all the many hundreds of agonistic and antagonistic analogues of the neurohypophysial peptides that have been reported contain an intact ring. Here we report that an intact ring is not essential for binding of antagonistic AVP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Very recently, a new series of antagonists lacking the usual hexapeptide ring structure have been synthesized (Manning et al, 1987b(Manning et al, , 1990Schmidt et al, 1991). Some of these linear ligands were very high affinity vasopressin antagonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, a new series of antagonists lacking the usual hexapeptide ring structure have been synthesized (Manning et al, 1987b(Manning et al, , 1990Schmidt et al, 1991). Some of these linear ligands were very high affinity vasopressin antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…More recent developments in the design of VPR antagonists have shown that linear analogues of [Arg'IVP can also bind with high affinity to VPR (Manning et al, 1987b(Manning et al, , 1990Schmidt et al, 1991). One such peptide, (PhAcAVP; [l-phenylacetyl, 2-O-methyl-D-tyrosine, 6-arginine, 8-arginine, 9-tyrosinamide]vasopressin) is a very high-affinity and V1,-selective antagonist (Schmidt et al, 1991).…”
mentioning
confidence: 99%
“…Arginine VP and the VP receptor antagonists were obtained from Bachem (Torrence, CA). The receptor antagonists were selected on the basis of their affinity for the V 1 and/or V2 receptors (24)(25)(26)(27). Peptides were dissolved in sterile 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Peptides were dissolved in sterile 0.9% NaCl. The antagonists were administered in doses of 0 ng (isotonic saline), 10 8,9 ]VP (TVA-AVP), which is one of the most potent V2 receptor antagonists (25,26).…”
Section: Methodsmentioning
confidence: 99%
“…The selective antagonists [deamino-Pen(1), O-Me-Tyr(2), Arg(8)]-vasopressin (V-1880; Lot # 053K13071; Sigma, St Louis, MO, USA) and [adamantaneacetyl(1), O-Et-DTyr(2), Val(4), Aminobuturyl(6), Arg(8,9)]-vasopressin (V-2381; Lot # 073K11151; Sigma, St Louis, MO, USA) were used for inhibition of V 1 and V 2 receptors, respectively (Manning et al, 1987). One hundred or 500 ng of the drugs in 2 mL saline were administered 5 mins after MCAO by intracerebroventricular administration (0.9 mm left, 0.1 mm posterior, and 3.1 mm deep relative to bregma).…”
Section: Application Of V 1 and V 2 Receptor Antagonistsmentioning
confidence: 99%